Young people's colour preference and the arousal level of small apartments. Issue 3 (15th November 2021) - Jiang, Ao; Yao, Xiang; Hemingray, Caroline; Westland, Stephen
Abstract: It is widely believed that people have preferences in relation to the colour of their interior environment. With the development of the global small apartment industry, it is important to understand well people's colour preference for apartments. This study investigated the apartment colour preference (N = 958) and the arousal level measured as heart rate variability for 70 young Chinese people for 21 colours. The findings indicate that young Chinese people (22‐27 years of age) prefer light red, red, yellow, and gray areas of the colour space, and least prefer darker colours in the green, gray, and brown areas of the colour space. In terms of heart rate variability arousal, it was found that colours in the red, purple, and yellow areas of the colour space had the highest effect on heart rate variability arousal, vs gray and brown colours, which were found to have the lowest effect on arousal levels.